1999
DOI: 10.1017/s002531549800099x
|View full text |Cite
|
Sign up to set email alerts
|

The phylum Sipuncula in the eastern Mediterranean: composition, ecology, zoogeography

Abstract: The bibliography concerning the Mediterranean Sipuncula is reviewed, particularly that from the eastern Mediterranean. Additional data are provided from macrobenthic samples collected between 1974 and 1997 in the Hellenic waters. A total of 17 species are recorded, five of which (Sipunculus norvegicus, Golfingia elongata, Nephasoma lilljeborgi, Thysanocardiacatharinae and Aspidosiphon (Akrikos) mexicanus) are reported for the first time in Hellenic waters. Three more species (Onchnesoma squamatum squamatum, As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…According to the Makra and Nicolaidou (2000) abundance of this Polychaeta species indicates the moderately disturbed areas of the inner Argolikos Bay. The highest abundance was accounted for a spinculid species Onchnesoma steenstrupi at 100 m as Tselepides et al (2000) stated O. steenstrupi was one of the most abundant species between 70 and 100 m (Murina et al 1999).…”
Section: Discussionmentioning
confidence: 95%
“…According to the Makra and Nicolaidou (2000) abundance of this Polychaeta species indicates the moderately disturbed areas of the inner Argolikos Bay. The highest abundance was accounted for a spinculid species Onchnesoma steenstrupi at 100 m as Tselepides et al (2000) stated O. steenstrupi was one of the most abundant species between 70 and 100 m (Murina et al 1999).…”
Section: Discussionmentioning
confidence: 95%
“…There are too few taxonomists to process all the work that needs to be done, especially within the lesser-known groups. For example, there are presently <10 specialists worldwide who are able to identify sipunculan worms properly (Murina et al 1999). Not only is it easier and cheaper to train personnel to sort to taxonomic levels higher than species, the risk of potential taxonomic classification error is also lower at a higher level of identification (Dauvin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Benthic community studies often neglect identifying sipunculan specimens to species level, predominately because of the limited number of sipunculan taxonomists worldwide (currently less than 10: Murina et al 1999). However, it is important that macrofaunal community studies do not overlook sipunculans and it is strongly recommended that specimens are identified to the species level (Kędra & Wl odarska-Kowalczuk 2008;Shields & Kędra 2009).…”
Section: Introductionmentioning
confidence: 99%